L'attention de la « créature isolée » à partir de l'expérience spatiale de János Pilinszky, à travers la « pureté parfaite » de Simone Weil, jusqu'à la « nuit obscure » de François Mauriac - Turai, Laura (Verbum – Analecta Neolatina, 2008)
The poetry of János Pilinszky was influenced by the philosophical mysticism of Simone Weil and by the atmosphere of the novels of Francois Mauriac. Their profoundly catholic vision of the world (expressed or inexpressed) is oriented to the universe and to the union of all creatures in three different ways, albeit absolutely authentic and essentially identical. In this paper, I will try to highlight these parallelisms through some notions which are very important in the works of the three authors. I set out from the state of deep solitude and isolation of the reviewed poems of the Hungarian poet János Pilinszky, touching upon the concepts of attention, obscurity, purity, grace and many others by a comparative analysis in a special circular way.